Recent advances in cowpea IPM in West Africa - Togola, Abou; Datinon, Benjamin; Laouali, Amadou; Traoré, Fousseni; Agboton, Cyriaque; Ongom, Patrick O.; Ojo, James A.; Pittendrigh, Barry; Boukar, Ousmane; Tamò, Manuele (Frontiers in Agronomy, 2023)
Cowpea is an important and climate-resilient grain legume for human and livestock nutrition worldwide. Its grains represent a valuable source of protein for rural families in Sub-Saharan Africa while its haulms offer nutritious fodder for livestock, especially, in the Sahel regions.Cowpea production, unfortunately, faces substantial challenges of field and storage insect pests which can cause up to 100% losses. The use of synthetic pesticides, although providing farmers with a good level of pest control, has underscored the critical need for the development of integrated pest management (IPM) alternatives, due to their detrimental effects on humans, animals and the environment. This review examines recent advances in West Africa in cowpea insect pest management (IPM) approaches, highlighting research on host plant resistance, biological control, biopesticides, good cultural practices, and on-farm participatory research and training undertaken to support sustainable cowpea production. Cowpea is one of the most critical, climate-resilient grain legumes for human and livestock nutrition but is subject to up to 100% field and storage losses in West Africa due to insect pests (primarily legume pod borers, cowpea aphids, flower bud thrips, pod-sucking bugs, and cowpea weevils). While synthetic pesticides have offered farmers some control, the human, animal, and environmental side effects of such pesticides have motivated the development of IPM alternatives, which have Numerous IPM options have been developed, tested and validated for combating cowpea insect problems in West Africa by research institutions and disseminated through farmer field schools (FFS), field demonstrations, training sessions, and community-based education. Reviewing these environmentally safer and scalable IPM innovations will provide cowpea stakeholders with insights into workable, sustainable solutions for minimizing crop pest problems, reducing reliance on harmful pesticides and ultimately ensuring the long-term viability of cowpea production and its contribution to food security.